2014
DOI: 10.1371/journal.pone.0086421
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Nanosecond Electric Fields In Vitro and In Vivo on Hepatocellular Carcinoma Indicate Macrophage Infiltration Contribute to Tumor Ablation In Vivo

Abstract: Background and AimRecurrence and metastasis are associated with poor prognosis in hepatocellular carcinoma even in the patients who have undergone radical resection. Therefore, effective treatment is urgently needed for improvement of patients' survival. Previously, we reported that nanosecond pulse electric fields (nsPEFs) can ablate melanoma by induction of apoptosis and inhibition of angiogenesis. This study aims to investigate the in vivo ablation strategy by comparing the dose effect of nanosecond electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 15 publications
0
35
2
Order By: Relevance
“…Use of the glycerol/NaHC0 3 gel should not significantly affect the penetration of the nsPEF or, as we also show (Figure ), affect the temperature generation, thereby strengthening the conclusion that the killing is primarily due to ROS/RNS and radicals. This conclusion does not refute other studies reporting nsPEF as a successful treatment for melanoma but only that the nsPEF associated with the generation of nsP DBD is not sufficient. Interestingly, a recent study showed when a μsPEF was applied in addition to plasma treatment, an enhanced antibacterial effect was observed .…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Use of the glycerol/NaHC0 3 gel should not significantly affect the penetration of the nsPEF or, as we also show (Figure ), affect the temperature generation, thereby strengthening the conclusion that the killing is primarily due to ROS/RNS and radicals. This conclusion does not refute other studies reporting nsPEF as a successful treatment for melanoma but only that the nsPEF associated with the generation of nsP DBD is not sufficient. Interestingly, a recent study showed when a μsPEF was applied in addition to plasma treatment, an enhanced antibacterial effect was observed .…”
Section: Discussioncontrasting
confidence: 93%
“…The effective selectivity of the cancer cells to ROS‐induced death has been attributed their higher metabolic rate which makes them significantly more susceptible to oxidative stress when compared to normal cells . The effective killing of cancer cells using nsP electric field treatment has also been attributed to the stimulation of apoptosis, pyknosis, and DNA fragmentation both in vitro and in vivo. Studies report nsPEF treatment can be used to ablate melanoma, with evidence of destruction of the tumor blood supply and complete remission after nsPEF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have shown that nsPEF has extensive biological effects in colon cancer [26][27], ovarian cancer [28][29], oral cancer [30][31][32], pancreatic cancer [33], and brosarcoma [34]. In addition to inducing tumour cell apoptosis, nsPEF modulates tumour cell proliferation, invasion and metastasis, the tumour microenvironment, angiogenesis, and other tumour characteristics [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Nanosecond pulsed electric field (nsPEF) ablation originated from high voltage power technology and it showed potential in loco-regional tumor ablation [ 1 ]. NsPEF ablates tumors with ultra-short pulses by altering electrical conductivity and permeability of the tumor cell membrane, causing cell apoptosis [ 2 , 3 ]. Recently its potential in stimulating immune reaction was also reported [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%